Method for preparing highly ion-conductive sulfide-based solid electrolyte by dissolution-precipitation and composition used therein
By using composite solvents and heat treatment technology, the preparation of sulfide-based solid electrolytes is solved, and the problems of long treatment time and impurity residues are improved, and the conductivity and electrochemical stability of lithium ion are improved.
Patent Information
- Application Number
- CN201911088559.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-11-30
- Filing Date
- 2019-11-08
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2039-11-08
AI Technical Summary
In the prior art, when preparing sulfide-based solid electrolytes, the treatment time is long and impurities are easily residue, which affects the electrochemical stability of lithium ions.
Using the composite solvent, a first solvent with a cyano group and a second solvent with a polarity index less than 4, the composite solvent is removed and heat-treated to form sulfide precipitation and crystallization to avoid side reactions and impurities. .
The preparation time is shortened, impurity residue is reduced, and the lithium ion conductivity and electrochemical stability of the sulfide-based solid electrolyte are improved.
Smart Images

Figure CN111261933B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for preparing a highly ion-conductive sulfide-based solid electrolyte using dissolution-precipitation and a composition used therefor. Background Art
[0002] Secondary batteries that can be charged and discharged are used in large transportation vehicles such as hybrid vehicles and electric vehicles, as well as small electronic devices such as mobile phones and notebook computers. Therefore, it is necessary to develop secondary batteries with higher stability and energy density.
[0003] Secondary batteries are manufactured based on organic solvents (eg, organic liquid electrolytes), and thus there is a limit to the extent to which their stability and energy density can be improved.
[0004] Meanwhile, all-solid-state batteries using inorganic solid electrolytes are based on a technology that avoids organic solvents. Therefore, safer and simpler all-solid-state batteries can be manufactured, and therefore all-solid-state batteries have attracted considerable attention in recent years.
[0005] Solid electrolytes are divided into oxide-based solid electrolytes and sulfide-based solid electrolytes. Sulfide-based solid electrolytes show higher lithium ion conductivity than oxide-based solid electrolytes. In addition, sulfide-based solid electrolytes show high ductility. Therefore, sulfide-based solid electrolytes have processing flexibility, and thus sulfide-based solid electrolytes can be used for various purposes. U.S. Patent Application Publication No. US2015 / 0093652 discloses a method for preparing a sulfide solid electrolyte.
[0006] The above information disclosed in this Background section is only provided for enhancement of understanding of the background of the invention and therefore it may contain information that does not form the prior art that is already known in this country to a person of ordinary skill in the art. Summary of the invention
[0007] One aspect of the present invention is to provide a method for manufacturing a highly ion-conductive sulfide-based solid electrolyte and a composition therefor, which can reduce processing time and prevent impurities from remaining in a final product.
[0008] One aspect of the present invention provides a composition for preparing a sulfide-based solid electrolyte, the composition comprising a composite solvent and a raw material, the composite solvent comprising a first solvent containing a cyano group and a second solvent having a polarity index less than 4, the raw material comprising lithium sulfide (Li 2 S) and phosphorus pentasulfide (P 2 S 5 ).
[0009] The first solvent may be acetonitrile.
[0010] The second solvent may be selected from the group consisting of isopropanol, 2-butanol, and combinations thereof.
[0011] The composite solvent may include greater than or equal to 99.975 wt % and less than 100 wt % of the first solvent and greater than 0 wt % and less than or equal to 0.025 wt % of the second solvent.
[0012] The raw material may further contain lithium halide (LiX, wherein X is a halogen element).
[0013] The raw material may contain 50 mol% to 62.5 mol% of lithium sulfide (Li 2 S), 12.5 mol% to 20 mol% of phosphorus pentasulfide (P 2 S 5 ) and 25 mol % to 37.5 mol % of lithium halide (LiX).
[0014] Another aspect of the present invention provides a method for preparing a sulfide-based solid electrolyte, the method comprising preparing a composite solvent, the composite solvent comprising a first solvent containing a cyano group and a second solvent having a polarity index less than 4; 2 S) and phosphorus pentasulfide (P 2 S 5 ) into a composite solvent; and stirring the raw material to obtain a sulfide precipitate.
[0015] The method may further include removing the complex solvent.
[0016] The method may further include heat-treating the sulfide precipitate to crystallize the sulfide precipitate after removing the complex solvent.
[0017] The first solvent may be acetonitrile.
[0018] The second solvent may be selected from the group consisting of isopropanol, 2-butanol, and combinations thereof.
[0019] The composite solvent may include greater than or equal to 99.975 wt % and less than 100 wt % of the first solvent and greater than 0 wt % and less than or equal to 0.025 wt % of the second solvent.
[0020] The raw material may further contain lithium halide (LiX, wherein X is a halogen element).
[0021] The raw material may contain 50 mol% to 62.5 mol% of lithium sulfide (Li 2 S), 12.5 mol% to 20 mol% of phosphorus pentasulfide (P 2 S 5 ) and 25 mol % to 37.5 mol % of lithium halide (LiX).
[0022] The stirring may be performed at a temperature of 30 to 80°C.
[0023] The stirring may include a first stirring performed at 100 to 150 rpm for 5 to 10 minutes and a second stirring performed at 250 to 300 rpm for 18 to 48 hours.
[0024] The first stirring and the second stirring may be performed continuously.
[0025] The complex solvent may be removed by vacuum drying at 30 to 80° C. for 1 to 24 hours.
[0026] The sulfide precipitate may be crystallized by heat treatment at 300 to 550° C. and for 1 to 48 hours.
[0027] The sulfide-based solid electrolyte may have an argyrodite-type crystal structure.
[0028] Other aspects and embodiments of the invention are discussed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The above and other features of the present invention will now be described in detail with reference to embodiments thereof shown in the accompanying drawings, which are given below by way of illustration only and therefore do not limit the present invention, and in which:
[0030] Figure 1 is a diagram showing a method for manufacturing a sulfide-based solid electrolyte according to an embodiment of the present invention;
[0031] FIG. 2A to FIG. 2E is a graph showing the results of X-ray diffraction analysis of the sulfide-based solid electrolytes according to Examples 1 and 2 and Comparative Examples 1 to 3;
[0032] Figure 3 is a graph showing the results of Raman spectroscopy analysis of the sulfide-based solid electrolytes according to Examples 1 and 2 and Comparative Examples 2 and 3;
[0033] Figure 4A and Figure 4B is a graph showing the results of cyclic voltammetry for evaluating the voltage stability of the sulfide-based solid electrolytes according to Examples 1 and 2; and
[0034] Figure 5 is a graph showing the measurement results of the capacities of all-solid-state batteries including the sulfide-based solid electrolytes according to Examples 1 and 2.
[0035] It should be understood that the accompanying drawings are not necessarily drawn to scale, presenting a somewhat simplified representation of various features illustrating the basic principles of the invention. The specific design features of the present invention disclosed herein, including, for example, specific dimensions, orientations, locations, and shapes, will be determined in part by the specific intended application and use environment.
[0036] In the drawings, reference numbers refer to the same or equivalent parts of the present invention throughout the several figures of the drawing. DETAILED DESCRIPTION
[0037] The various aspects, features and advantages of the present invention will be clearly understood from the embodiments with reference to the accompanying drawings. However, the present invention is not limited to the embodiments and can be implemented in different forms. The proposed embodiments are only intended to provide a thorough and complete understanding of the disclosed content and are sufficient to inform those skilled in the art of the technical concept of the present invention.
[0038] Throughout the description of the accompanying drawings, the same reference numerals refer to the same elements. In the accompanying drawings, for clarity, the size of the structure is exaggerated. It should be understood that although the terms "first", "second", etc. can be used herein to describe various elements, the corresponding elements should not be interpreted as being limited by these terms and are only used to distinguish one element from another. For example, within the scope of the present invention, the first element may be referred to as the second element, and similarly, the second element may be referred to as the first element. Unless the context clearly indicates otherwise, the singular form is also intended to include the plural form.
[0039] It should also be understood that the terms "including", "having", etc., when used in this specification, specify the presence of the features, numbers, steps, operations, elements, components, or combinations thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, operations, elements, components, or combinations thereof. In addition, it should be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element, or there can be intermediate elements. It should also be understood that when an element such as a layer, film, region, or substrate is referred to as being "under" another element, it can be directly under the other element, or there can be intermediate elements.
[0040] Unless the context clearly indicates otherwise, all numbers, graphics and / or expressions representing the amount of components, reaction conditions, polymer compositions and mixtures used in this specification are approximate values, which reflect the various uncertainties of measurement inherently occurring when obtaining these numbers, etc. For this reason, it should be understood that in all cases, the term "about" should be understood to modify all numbers, graphics and / or expressions. In addition, when numerical ranges are disclosed in the specification, these ranges are continuous and include all numbers from the minimum value to the maximum value, including the maximum value in the range, unless otherwise defined. In addition, when the range is referred to as an integer, it includes all integers from the minimum value to the maximum value, including the maximum value in the range, unless otherwise defined.
[0041] One embodiment of preparing a sulfide solid electrolyte provides a method of making lithium sulfide (Li 2 S) and phosphorus pentasulfide (P 2 S 5 ) in a polar organic solvent, which is suitable for mass production of sulfide-based solid electrolytes. However, the above method has the disadvantage of increasing the processing time. In addition, unlike the mechanical grinding method, since the above method aims to produce a sulfide-based solid electrolyte by chemical reaction of the starting materials, it is not easy to remove low-solubility materials such as lithium sulfide (Li 2 S) impurities and organic residues. Therefore, a large amount of lithium sulfide (Li 2 S) remains in the final product. The residual lithium sulfide reacts with moisture and reduces the electrochemical stability of lithium.
[0042] refer to Figure 1 The method for preparing a sulfide-based solid electrolyte according to an embodiment of the present invention includes the steps of preparing a composite solvent (S1), the composite solvent comprising a first solvent containing a cyano group and a second solvent having a polarity index less than 4; 2 S) and phosphorus pentasulfide (P 2 S 5 ) into a composite solvent to form a mixture; stirring the mixture to obtain a sulfide precipitate (e.g., Li 6 PS 5 Cl) step (S3); a step of removing the composite solvent (S4) and a step of heat treating the sulfide precipitate to crystallize the sulfide precipitate (S5).
[0043] The composite solvent may include a first solvent having a relatively high polarity index and a second solvent having a relatively low polarity index. Herein, the term "polarity index" generally refers to the degree of polarity of a solvent, ranging from 0 (indicating non-polarity) to 10.
[0044] The first solvent may be an aprotic solvent having a high polarity index. Specifically, the first solvent may be a solvent including a cyano group and having a polarity index of 5 or higher. More specifically, the first solvent may be acetonitrile. The polarity index of acetonitrile is 5.8.
[0045] As for the raw materials, phosphorus pentasulfide (P 2 S 5 ) is soluble in the first solvent, while lithium sulfide (Li 2 When the raw material is stirred in the first solvent, lithium sulfide (LiS) is insoluble in the first solvent. 2 S) particles and phosphorus pentasulfide (P 2 S 5 ) react with each other to form sulfide precipitation. 2 S or LiCl) has low solubility and thus may generate impurities.
[0046] In an embodiment of the present invention, a small amount of a second solvent with a relatively low polarity index, such as an alcohol-based solvent, is added to the second solvent to prevent the occurrence of this side reaction. For the first solvent, due to the high dipole moment, a dipole-dipole interaction occurs. When a solvent with a polarity index less than 4 is added to the first solvent, the dipole-dipole interaction weakens, thereby preventing the occurrence of side reactions. In addition, the solubility of the precursor increases, so that the barrier energy required to form a crystalline structure is reduced, thereby preventing side reactions.
[0047] The second solvent may be an alcohol-based solvent having a polarity index of less than 4 and including a hydroxyl group. Specifically, the second solvent may be selected from the group consisting of isopropyl alcohol (IPA), 2-butanol, and a combination thereof. Isopropyl alcohol (IPA) has a polarity index of 3.9, and 2-butanol has a polarity index of 3.8.
[0048] The composite solvent may include a first solvent greater than or equal to 99.975wt% and less than 100wt% and a second solvent greater than 0wt% and less than or equal to 0.025wt%. In an embodiment, the content of the second solvent is equal to or less than 0.025wt% to avoid or minimize the possibility of the second solvent as an impurity. When the second solvent is an impurity, the sulfide-based solid electrolyte may be unevenly composed, or the composition of the raw material may deviate stoichiometrically, thereby possibly generating impurities.
[0049] The raw material may include lithium sulfide (Li 2 S) and phosphorus pentasulfide (P 2 S 5 ). Lithium sulfide (Li 2 S) and phosphorus pentasulfide (P 2 S5 ) are not particularly limited in content. However, preferably, the raw material includes 60 mol% to 80 mol% of lithium sulfide (Li 2 S) and 20 mol% to 40 mol% of phosphorus pentasulfide (P 2 S 5 ).
[0050] In addition, the raw material may contain 50 mol% to 62.5 mol% of lithium sulfide (Li 2 S), 12.5 mol% to 20 mol% of phosphorus pentasulfide (P 2 S 5 ) and 25 mol % to 37.5 mol % of lithium halide (LiX).
[0051] The lithium halide may be selected from the group consisting of LiCl, LiBr, LiI and combinations thereof. Preferably, the lithium halide is LiCl.
[0052] The composition for preparing a sulfide-based solid electrolyte according to an embodiment of the present invention includes a composite solvent and a raw material. When stirred, the composition is used to perform the following description to obtain a sulfide-based solid electrolyte. The composite solvent and the raw material are previously described, so further description thereof will be omitted.
[0053] When the mixture of the raw material and the composite solvent is stirred, as described above, the raw material reacts in the solvent medium to form and precipitate an amorphous sulfide-based solid electrolyte (S3). In this specification, the amorphous sulfide-based solid electrolyte is referred to as a sulfide precipitate. The composite solvent can be supplied to a reactor or chamber having a stirring blade of a predetermined shape, the raw material can be introduced into the composite solvent, and the stirring blade can be rotated for stirring.
[0054] Stirring can be carried out at a temperature of 30 to 80° C. If the stirring temperature is too low, the raw materials may not react fully. In an embodiment, the stirring temperature is equal to or greater than 30° C. to allow the raw materials to react fully. If the stirring temperature is too high, side reactions may occur, which may produce impurities. In an embodiment, in order to allow the raw materials to react fully, the stirring temperature is equal to or greater than 30° C., and in order to avoid side reactions that may produce impurities, the stirring temperature is equal to or less than 80° C.
[0055] In addition, the first stirring may be performed under the conditions of 100 to 150 rpm and 5 to 10 minutes, and the second stirring may be performed under the conditions of 250 to 300 rpm and 18 to 48 hours.
[0056] The first stirring is performed in order to uniformly mix the raw materials and prevent the raw materials from sticking. To this end, the first stirring must be performed in a state where the above conditions are met.
[0057] The second stirring is carried out in order to control the particle diameter of sulfide precipitation. When the stirring speed of the second stirring is 250 to 300rpm, the particle diameter of sulfide precipitation is the most uniform. If the stirring time of the second stirring is too short, the raw material may not be able to fully react. If the stirring time of the second stirring is too long, the processing time may be excessively increased, and side reactions may occur, thereby possibly producing impurities. In an embodiment, the stirring time of the second stirring is equal to or greater than 18 hours, so that the raw material and the solvent fully react, and the stirring time of the second stirring is equal to or less than 48 hours, to avoid or minimize the excessive increase of the processing time, and the occurrence of side reactions that may cause the generation of impurities.
[0058] In an embodiment, the first stirring and the second stirring are performed continuously to improve the processing convenience and shorten the processing time. However, the present invention is not limited thereto. Due to the addition of additives or for processing reasons, the first stirring and the second stirring may be performed intermittently.
[0059] After the sulfide precipitate is obtained by stirring, the composite solvent may be removed ( S4 ).
[0060] The composite solvent may be removed by vacuum drying at 30 to 80° C. and for 1 to 24 hours. The above conditions must be met in order to prevent or suppress the generation of impurities due to side reactions.
[0061] In an embodiment, vacuum drying is performed to prevent or inhibit the sulfide precipitate from coming into contact with air, since the sulfide precipitate reacts even with moisture in the air.
[0062] After removing the composite solvent, the sulfide precipitate can be crystallized by heat treatment (S5). As described above, the sulfide precipitate is an amorphous sulfide-based solid electrolyte. When the sulfide precipitate is heat treated at a specific temperature for a specific time, the atomic arrangement of the sulfide precipitate changes to a regular one, so that the sulfide precipitate has a specific crystalline structure.
[0063] The heat treatment may be performed under conditions of 300 to 550° C. and 1 to 48 hours. In addition, the heat treatment may be performed in an inert atmosphere such as argon or nitrogen or in a vacuum atmosphere. In the case where the sulfide precipitate is heat treated under the above conditions, a crystalline sulfide-based solid electrolyte having a crystalline phase of an argyrodite-type crystal structure may be obtained.
[0064] As described above, the present invention relates to a method for using new raw materials to form a sulfide-based solid electrolyte with a novel composition. Hereinafter, the present invention will be described in more detail with reference to specific embodiments. However, the following embodiments are only for the purpose of helping to understand the present invention, and the present invention is not limited by the following embodiments.
[0065] Example 1
[0066] (S1) 0.025 wt % of isopropyl alcohol (IPA), which is an alcohol-based solvent (second solvent) having a polarity index of 3.9, was added to 99.975 wt % of acetonitrile (first solvent) and mixed at 150 rpm for about 10 minutes to prepare a composite solvent.
[0067] (S2) will contain lithium sulfide (Li 2 S), phosphorus pentasulfide (P 2 S 5 ) and lithium chloride (LiCl) are introduced into a composite solvent. At this time, the raw materials are weighed and introduced to obtain a final product according to the following Chemical Formula 1, that is, a sulfide-based solid electrolyte.
[0068] [Chemical formula 1]
[0069] Li 6 PS 5 Cl
[0070] (S3) Firstly, the raw material is stirred at 150 rpm for 5 minutes, and then the raw material is stirred for a second time at 280 rpm for 24 hours to obtain a sulfide precipitate. The first stirring and the second stirring are performed continuously.
[0071] (S4) After the stirring is completed, vacuum drying is performed at ambient temperature (25° C.) for about 24 hours to remove the composite solvent.
[0072] (S5) After removing the composite solvent, the sulfide precipitate is heat treated at 550° C. for 5 hours to obtain a crystalline sulfide-based solid electrolyte.
[0073] Example 2
[0074] A crystalline sulfide-based solid electrolyte was prepared using the same method as in Example 1, except that 2-butanol having a polarity index of 3.8 was used as the second solvent.
[0075] Comparative Example 1:
[0076] A crystalline sulfide-based solid electrolyte was prepared using the same method as in Example 1, except that 1-propanol having a polarity index of 4 was used as the second solvent.
[0077] Comparative Example 2:
[0078] A crystalline sulfide-based solid electrolyte was prepared using the same method as in Example 1, except that ethanol having a polarity index of 5.2 was used as the second solvent.
[0079] Comparative Example 3:
[0080] A crystalline sulfide-based solid electrolyte was prepared using the same method as in Example 1, except that only acetonitrile was used as a single solvent, and no second solvent was used.
[0081] Experimental Example 1 - Determination of Lithium Ion Conductivity
[0082] The ionic conductivity of each sulfide-based solid electrolyte according to Examples 1 and 2 and Comparative Examples 1 to 3 was measured. Specifically, each sulfide-based solid electrolyte was compressed to form a sample for measurement (13 mm in diameter and 1 to 1.5 mm in thickness). An alternating current potential of 10 mV was applied to the sample in an oven where ambient temperature was maintained, and then 1×10 6 The frequency was scanned to 1 Hz to measure the impedance value, from which the ionic conductivity was determined. The results are shown in Table 1 below.
[0083] [Table 1]
[0084]
[0085] Referring to Table 1 above, it can be seen that each of the sulfide-based solid electrolytes prepared according to Examples 1 and 2 has a very high lithium ion conductivity. For reference, the sulfide-based solid electrolyte disclosed in U.S. Patent Application Publication No. US 2015 / 0093652 (wherein the sulfide-based solid electrolyte is prepared by using dissolution precipitation) has a lithium ion conductivity of 1.0 mS / cm, which is much lower than the lithium ion conductivity of each of the sulfide-based solid electrolytes prepared according to Examples 1 and 2.
[0086] Referring to the results of Comparative Examples 1 and 2, it can be seen that when an alcohol-based solvent having a polarity index of 4 or more is used as the second solvent, the lithium ion conductivity is greatly reduced. The reason for this is that too many side reactions occur, thereby generating impurities, which can be more clearly understood from the results of X-ray diffraction analysis, which will be described below.
[0087] In addition, referring to the results of Comparative Example 3, it can be seen that when only acetonitrile is used, the dipole-dipole interaction caused by its high dipole moment cannot be weakened, so that side reactions occur and impurities are generated, or the reduction of Li 2 The solubility of the S or LiCl precursor cannot prevent the generation of impurities.
[0088] Experimental Example 2 - X-ray Diffraction (XRD) Analysis
[0089] XRD analysis was performed on the sulfide-based solid electrolytes according to Examples 1 and 2 and Comparative Examples 1 to 3. The results are shown in FIG. 2A to FIG. 2E middle.
[0090] Figure 2A The results of Example 1 are shown. Figure 2B The results of Example 2 are shown. Figure 2C The results of Comparative Example 1 are shown. Figure 2D The results of Comparative Example 2 are shown, and Figure 2E The results of Comparative Example 3 are shown.
[0091] refer to Figure 2A and Figure 2B It can be seen that each of the sulfide-based solid electrolytes prepared according to Examples 1 and 2 does not contain any Li 3 PO 4 Or impurities of LiCl.
[0092] On the contrary, reference FIG. 2C to FIG. 2E , it can be seen that a large amount of impurity Li was detected 3 PO 4 and LiCl.
[0093] Therefore, it can be seen that when a sulfide-based solid electrolyte is prepared using the method and composition according to an embodiment of the present invention, the occurrence of side reactions can be prevented or minimized, so that no impurities remain in the sulfide-based solid electrolyte.
[0094] Experimental Example 3-Raman spectroscopy analysis
[0095] Raman spectroscopy analysis was performed on the sulfide-based solid electrolytes according to Examples 1 and 2 and Comparative Examples 1 to 3. Each sample was placed on a sealed holder, and an argon ion laser with a wavelength of 514 nm was irradiated on the sample to measure the molecular vibration spectrum of the sample for 60 seconds. The results are shown in FIG. Figure 3 shown.
[0096] It can be seen that no negative ion clusters with substituted oxygen were found in each of the sulfide-based solid electrolytes prepared according to Examples 1 and 2, and thus no negative ion clusters such as Li 3 PO 4 In addition, it can be seen that from the formation of PS 4 3- Initially, each sulfide-based solid electrolyte includes a crystalline phase having an argyrodite-type crystal structure.
[0097] In contrast, it can be seen that negative ion clusters PS4 having substituted oxygen are formed in the sulfide-based solid electrolyte prepared according to Comparative Example 2. - n O n , resulting in Li as an impurity 3 PO 4 .
[0098] In addition, it can be seen that from the formation of PS 4 3- The sulfide-based solid electrolyte prepared according to Comparative Example 3 initially includes a crystalline phase having an argyrodite-type crystal structure, but forms Li 2 S, so that impurities remain.
[0099] Experimental Example 3 - Evaluation of Voltage Stability
[0100] Cyclic voltammetry of the voltage stability of each sulfide-based solid electrolyte prepared according to Examples 1 and 2 was evaluated. Indium metal was attached to a sample of each sulfide-based solid electrolyte as in Experimental Example 1, and cyclic voltammetry of the voltage stability of each sulfide-based solid electrolyte in the range of -1V to 5V was measured under the condition of 20mV / s. The results are shown in Figure 4A and Figure 4B .
[0101] Figure 4A The results of Example 1 are shown, and Figure 4B The results of Example 2 are shown.
[0102] Referring to these figures, no decomposition reaction occurs until a high voltage of 5 V, so it can be seen that in the case where the sulfide-based solid electrolyte according to an embodiment of the present invention is used, it is an electrochemically stable all-solid-state battery with a sulfide-based solid electrolyte.
[0103] Experimental Example 5 - Capacity Evaluation
[0104] All-solid-state batteries were prepared using the sulfide-based solid electrolytes according to Examples 1 and 2, and the capacity of each of the all-solid-state batteries was measured.
[0105] Specifically, 0.2 g of each sulfide-based solid electrolyte was palletized using a mold having a diameter of 6 Φ to produce a solid electrolyte layer. 0.02 g of a 70 wt % LiNi 0.6 Co 0.2 Mn 0.2 O 2 A mixture of (positive electrode active material), 28 wt% of sulfide-based solid electrolyte and 2 wt% of Super-P (conductive agent) was applied to one surface of the solid electrolyte layer to prepare a positive electrode. An indium foil was attached to the other surface of the solid electrolyte layer to prepare a negative electrode.
[0106] Compared with Li, the all-solid-state battery prepared according to the above description was charged and discharged at a rate of 0.1C and a voltage of 3.0V to 4.3V. Figure 5Referring to the figure, it can be seen that the capacities of the all-solid-state batteries prepared using the sulfide-based solid electrolytes according to Examples 1 and 2 are about 120 mAh / g and about 140 mAh / g, respectively.
[0107] As is apparent from the foregoing, the processing time required to prepare the sulfide-based solid electrolyte can be reduced. In addition, no impurities remain in the final product, thereby improving the ionic conductivity and electrochemical stability of the sulfide-based solid electrolyte.
[0108] The effects of the present invention are not limited to those described above. It should be understood that the effects of the present invention include all effects that can be inferred from the foregoing description of the present invention.
[0109] The invention has been described in detail with reference to its embodiments. However, those skilled in the art will appreciate that changes may be made to these embodiments without departing from the principles and spirit of the invention, the scope of the disclosure being defined by the appended claims and their equivalents.
Claims
1. A composition for preparing a sulfide-based solid electrolyte, the composition comprising: A composite solvent comprising a first solvent containing a cyano group and a second solvent having a polarity index less than 4; and A raw material comprising lithium sulfide and phosphorus pentasulfide, wherein the first solvent is acetonitrile, wherein the second solvent is selected from the group consisting of isopropanol, 2-butanol and combinations thereof, The composite solvent comprises greater than or equal to 99.975 wt % and less than 100 wt % of the first solvent and greater than 0 wt % and less than or equal to 0.025 wt % of the second solvent.
2. The composition of claim 1, wherein the raw material further comprises a lithium halide.
3. The composition of claim 2, wherein the raw material comprises 50 mol% to 62.5 mol% of lithium sulfide, 12.5 mol% to 20 mol% of phosphorus pentasulfide, and 25 mol% to 37.5 mol% of lithium halide.
4. A method for preparing a sulfide-based solid electrolyte, the method comprising: preparing a composite solvent comprising a first solvent containing a cyano group and a second solvent having a polarity index less than 4; introducing a raw material comprising lithium sulfide and phosphorus pentasulfide into the composite solvent to form a mixture; and stirring the mixture to obtain a sulfide precipitate, wherein the first solvent is acetonitrile, wherein the second solvent is selected from the group consisting of isopropanol, 2-butanol and combinations thereof, The composite solvent comprises greater than or equal to 99.975 wt % and less than 100 wt % of the first solvent and greater than 0 wt % and less than or equal to 0.025 wt % of the second solvent. The method according to claim 4 , further comprising removing the composite solvent. 6 . The method according to claim 5 , further comprising, after removing the complex solvent, heat-treating the sulfide precipitate to crystallize the sulfide precipitate.
7. The method of claim 4, wherein the raw material further comprises a lithium halide.
8. The method according to claim 7, wherein the raw material comprises 50 mol% to 62.5 mol% of lithium sulfide, 12.5 mol% to 20 mol% of phosphorus pentasulfide, and 25 mol% to 37.5 mol% of lithium halide.
9. The method according to claim 4, wherein the stirring is performed at a temperature of 30°C to 80°C. 10 . The method according to claim 4 , wherein the stirring comprises a first stirring performed at 100 to 150 rpm for 5 to 10 minutes and a second stirring performed at 250 to 300 rpm for 18 to 48 hours. The method according to claim 10 , wherein the first stirring and the second stirring are performed continuously.
12. The method according to claim 4, wherein the composite solvent is removed by vacuum drying at 30°C to 80°C and for 1 hour to 24 hours.
13. The method of claim 4, wherein the sulfide precipitate is crystallized by heat treatment at 300°C to 550°C and for 1 hour to 48 hours.
14. The method according to claim 6, wherein the sulfide-based solid electrolyte has an argyrodite-type crystal structure.
Citation Information
Patent Citations
Sulfide solid electrolyte, method of preparing the same, and solid state battery including the same
US20150093652A1
Manufacturing method for solid electrolyte sheet
CN102005608A
Sulfide electrolyte material and preparation method thereof
CN103500853A